Analysis of job stress during the COVID-19 pandemic on teacher performance - Lumbanraja, Pretty Luci; Lumbanraja, Penny Chariti; Lumbanraja, Sindak Panaili (Universitas Pendidikan Nasional, 2024)
The COVID-19 pandemic that hit Indonesia caused many people to feel excessively anxious and fearful of uncertainty, impacting their work productivity. Individuals experienced behavioral, physical, and psychological symptoms such as headaches, difficulty sleeping, and other physical disorders, which are indicative of stress. While stress does not always have a negative meaning, excessive stress had an effect on work concentration. Work stress resulted in delays in work, decreased ability to carry out tasks, and even reduced performance. This research utilized quantitative methods, including questionnaires, interviews, and observations of teachers in Bilah Hulu District, Labuhan Batu Regency. Hypothesis testing was conducted using SEM analysis at a 95% confidence level (alpha = 0.05) with 17 research respondents. The results of the study showed that work stress had a negative and insignificant effect on teacher performance, indicating that higher stress levels among teachers reduced their performance, albeit weaklyin this study. The results also indicated that physical symptoms were the primary indicator of the work stress construct, while the quality of working conditions best described good teacher performance.